2014
DOI: 10.5296/ijl.v6i3.4553
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Krama Inggil (Javanese Language) in Family Domain at Semarang and Pekalongan Cities

Abstract: This descriptive study aimed to capture the natural use of Javanese language called krama inggil in the family domain, at Semarang and Pekalongan cities. The research method used was a qualitative method. Qualitative methods led researchers to be welcomed without prejudice in the form of speech that receives the case, the researcher emphasize the subjective aspects of the behavior of native speakers in order to understand the circumstances that exist in the form of speech research areas.The research findings o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
3
0
2
Order By: Relevance
“…For example, it was found that among families in the cities of Pekalongan and Semarang, there was a reluctance to use krama alus and krama [12]. Meanwhile, in the use of krama alus, errors often occur in unggah-ungguh (correct & polite usage) in the use of krama inggil and krama andhap, in which krama andhap is used for others while krama inggil is used for oneself, as shown the previous example.…”
Section: B Implication For Language Conservationmentioning
confidence: 85%
“…For example, it was found that among families in the cities of Pekalongan and Semarang, there was a reluctance to use krama alus and krama [12]. Meanwhile, in the use of krama alus, errors often occur in unggah-ungguh (correct & polite usage) in the use of krama inggil and krama andhap, in which krama andhap is used for others while krama inggil is used for oneself, as shown the previous example.…”
Section: B Implication For Language Conservationmentioning
confidence: 85%
“…The selected respondents will be the informants. The selection of informants will be carried out in a guided manner and certain criteria [9].…”
Section: Methodsmentioning
confidence: 99%
“…The phenomenon of decreasing interest in the use of Javanese language is getting eroded because it is eroded by the use of foreign languages. The trigger factors are low vocabulary mastery, lack of vocabulary sorting skills, and low understanding of Javanese uploads [21]. In order to prevent the decline in the quality of Javanese language mastery and politeness possessed by students, the revitalization of the independent learning curriculum was carried out.…”
Section: Implementation Of the Regional Language Curriculum In The In...mentioning
confidence: 99%